Kajian Teknis Produktivitas Belt Conveyor Jalur 7.1 Dalam Pengiriman Limestone Ke Storage Indarung VI pada PT. Semen Padang, Sumatera Barat - Jordi Andika Putra Salim; Yoszi Mingsi Anaperta; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2023)
PT Semen Padang is the oldest company in Indonesia which was founded in 1910. The basic ingredients for making cement are 81% Limestone, 9% Silica, 8.5% Clay, 1% Iron Sand and 0.5% Gypsum. PT Semen Padang conducts Silica and Limestone mining business in Bukit Karang Putih, Indarung, Lubuk Kilangan District, Padang City. In mining at PT Semen Padang there is a conveying activity in which in this activity the transportation of material that has been crushed is transported to storage. There are many types of storage for Padang Cement, starting from Indarung II, III, IV, V and VI. In conveying activities at Semen Padang there are 2 lines, namely the old line and the new line which is called the longbelt. At PT Semen Padang, belt conveyors come in a variety of sizes, and depending on the route taken for delivery, the capacity of each belt for the delivery of raw materials varies. As a result, the minimum production capacity will determine the belt conveyor's production capacity. In the long term of five years, PT Semen Padang intends to expand its output objective to 12,300 tons in 2021. Longbelt delivery lines start from 6A1J03-6A1J04-6A1J05-6A1J06- 6A1J07-6A1J08-6A1J10 to storage indarung VI.